VIDEO PROMOSI WISATA KABUPATEN KERINCI - HARI YOGA PRATAMA, Dr. Syafwandi, M.Sn., Riri Trinanda, S.Pd., M.Sn. (DEKAVE : Jurnal Desain Komunikasi Visual, 2019)
This article is intended to get an effective and communicative video design to introduce and provide information about tourism in Kerinci District through promotional videos. Kerinci is the main tourist destination owned by Jambi Province, is an interesting tourist attraction in Kerinci, such as Mount Kerinci tourism, Khayangan Hill, Lake Kerinci tourism, Telun Berasap waterfall tour, and also agro tourism, Tea Plantation. Tourism development is inseparable from communicative and informative promotions to be accessible to the wider community. Additional information about Kerinci tourism objects and also no use of visual communication media which consists of videos about the management of Kerinci attractions, making tourists or people outside the area do not know the details about tourism and what activities can be done on the tour.This promotional video was made using a qualitative research method using 5W + 1H analysis (what, who, when, where, why and how). This promotional video is also supported with several supporting media such as posters, x banners, T-shirts, totebags, stickers, mugs and backdrops.Keywords: Video, Promotion, Tourism, Kerinci